PERDAMAIAN DALAM PERSPEKTIF ISLAM DAN KRISTEN - Asy’ari Asy'ari (Al'Adalah, 2019)
The existence of Religion is a correction of behavioral problems that substantively cause tension, violence and even damage to the social fabric, or better known as tyranny. There is no religion established itself as a rel igion of violence and it is certain that all religions claim to be a religion of peace. But on the other hand, religion can lead to damage and even mass murder. Therefore, religious messages are ambivalent, whether religion is to solve problems or it is the source of problems. This ambivalence is emphasized with the rise of religious adherents by showing complex faces to interpret. The complex face is inseparable from the adherents of the r eligion itself, both Islam and Christian. Because the realizat ion of religious adherents have the legitimacy of the text (the source of their religious teachings).